Crisis of the educational process in marital conflict. A pedagogical study - Maria Teresa Moscato (University of Bologna, 2014)
The essay analyses in educational perspective the consequences of marital conflict on educational processes, exploring the social representations about family and education, and thus the dynamics of family conflict and of new reconstructed families. The A. examines also observable outcomes of the educational crisis, in term of school failure; social attitudes with respect to irregularities in familiar composition. The study attempts to outline some methodological principles for education and pedagogical advice. The research makes use of "gray material", as interview with adult and young people, formative teacher's group, and works - in the same time - to a critical reading of literature about these topics.